2021
DOI: 10.1039/d0ob02055a
|View full text |Cite
|
Sign up to set email alerts
|

C-5 selective chlorination of 8-aminoquinoline amides using dichloromethane

Abstract: An oxidant-free electrochemical regioselective chlorination of 8-aminoquinoline amides under ambient temperature in batch and continuous-flow was achieved. Inert DCM was used as the chlorinating reagent. Attributing to the continuous-flow setup,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The reported paired electrochemical halogenation reactions also use excessive halogen sources. 12,14 Finally, the electrophilic addition of 1 with Br 2 afforded brominated product 3 . The good compatibility and high site-selectivity of the C–H bromination may be due to sustained and low concentrations of Br 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The reported paired electrochemical halogenation reactions also use excessive halogen sources. 12,14 Finally, the electrophilic addition of 1 with Br 2 afforded brominated product 3 . The good compatibility and high site-selectivity of the C–H bromination may be due to sustained and low concentrations of Br 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As outlined in Figure 1 , cyclic voltammetry (CV) of 1,1-diphenylethylene substrate ( 1 ) (curve b) showed an oxidation peak at 2.48 V (vs. Ag/AgCl), which was higher than that of CH 2 Br 2 at 1.93 V (vs. Ag/AgCl) (curve c), so the comparison demonstrated that CH 2 Br 2 could be oxidized more easily than alkene substrate in this galvanostatic mode. It is reported that halogen anion X – and + CH 2 X cation could be generated via C–X bond cleavage of the CH 2 X 2 , 40 thus the involvement of free radical intermediate probably corresponded to the oxidation of Br – to Br • intermediate in curve c (1.93 V) for this electrolysis process.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 88%
“…Basing on preliminary mechanistic studies and literature reports, 27,[37][38]41 a plausible mechanism was proposed in Scheme 2. Initially, bromine anion Brand + CH2Br cation was gradually generated via C-X bond cleavage of the CH2Br2, 40 In summary, a protocol for electrochemical vicinal difunctionalization of various alkenes was well established in an undivided cell, which employed simple CH2Br2 and alcohol as bromine and alkoxy source without transition-metal mediator or exogenous oxidant. Therefore, it's a green and economical method to synthesize value-added β-bromoethers from cheap starting materials.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some electrochemical constructions of new C–N, C–O, C–S and C–Cl bonds were reported by us via a radical process. Lei reported an intramolecular oxidative annulation into substituted indoles (Scheme b-1).…”
Section: Introductionmentioning
confidence: 91%